The science of agricultural law in Poland. Reflections against the background of Western European science - Budzinowski, Roman (Przegląd Prawa Rolnego, 2019)
The fifteenth anniversary of the inclusion of Polish agriculture in the CAP mechanisms prompts one to make summaries and comparisons and formulate evaluations of the development of the science of agricultural law in the European context. The deliberations presented in the article are an attempt to formulate a few valid reflections, focusing on the comparison of the EU agricultural acquis, the general (theoretical) agricultural (national) law issues, traditional agricultural law issues, agri-food and agri-environmental law and rural development. As it is demonstrated in the article, the distance between the Polish science of agricultural law and Western European science has significantly narrowed. The issues undertaken by Polish agricultural lawyers fall within the scope of interest of their Western European counterparts. It may therefore be said that Polish agricultural lawyers are increasingly frequently becoming partners in research conducted by foreign scholars, and the use of their research and organisational potential may also be useful on an international forum.